Teachers in new situations during the COVID-19 period: impact on professional collaboration and quality of teaching - Hermína Gunnþórsdóttir; Berglind Gísladóttir; Ylfa Guðný Sigurðardóttir (Education in the North, 2021)
In late February of 2020 the first COVID-19 cases were confirmed in Iceland. The Icelandic government declared a four-week assembly ban, which included various restrictions that forced teachers to change their teaching methods and organisation. The aim of this study was to gain insight into the experience of teachers during this time and how it affected teachers' professional collaboration and teaching quality. COVID-19 restrictions in schools forced school leaders and teachers to react quickly and organise and implement students’ education according to constantly changing rules as the pandemic evolved. Teachers in each school were suddenly given new positions as entrepreneurs but at the same time were expected to maintain educational standards. These changed circumstances imposed new challenges within the schools, for example which competence criteria should be highlighted above others, which teaching methods should be used, what teaching platform to use and how to assess students’ work. Semi-structured interviews were conducted with thirteen teachers from three compulsory schools in Iceland in April 2020 at the peak of the first wave of the pandemic. Focus was placed on changes that affected teachers' professional collaboration, teaching quality and students’ learning. Findings indicate that teachers focused on “core subjects” and ignored other subjects, academic requirements were lowered, and teachers had to teach subjects that were not part of their specialization. The findings also show that some teachers experienced powerlessness and fear.